Culture and Mediterranean Diet - López M.T Iglesias (International Journal of Nutrition, 2019)
We discuss different aspects of the Mediterranean diet, including the historical, anthropological and cultural. The different foods that are characteristic of the Mediterranean diet are used to create all kinds of recipes, which are valued in gastronomic terms and are also highly nutritional. Bread, wine and extra virgin olive oil have been symbols of civilisation and prosperity for the peoples of the Mediterranean for thousands of years. The key elements of the Mediterranean diet are variety, moderation and the predominance of vegetables over food sourced from animals. These are complemented by a philosophy of life that values personal relationships, the pursuit of happiness and physical activity. A colourful cuisine has developed around the Mediterranean, which is rich and aromatic and which might be said to live in harmony with nature. The Mediterranean diet is about sharing, enjoying conversation around the table, and relaxing after the meal with a siesta. With the globalisation of food, the chronobiological rhythm of food intake has become skewed, and food industrialisation has led to the homogenisation of eating behaviours. The great chefs of today are artists, bold and dazzlingly creative, masters of harmony and subtlety, arousing hedonistic pleasures with this new form of artistic expression.
Keywords: Mediterranean diet